The Alzheimer's Prevention Registry: Accelerating recruitment and enrollment into Alzheimer's‐focused studies: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - High, Nellie M; Kettenhoven, Cassandra L; Graf, Hayley; Reiman, Eric M; Tariot, Pierre N; Langbaum, Jessica B
Abstract: Background: The Alzheimer's Prevention Initiative (API) is a collaborative program conducting preclinical Alzheimer's disease (AD) trials in people who are at elevated risk of developing AD symptoms. To support these and other trials, we developed the web‐based Alzheimer's Prevention Registry ("APR") program to provide resources to the AD scientific community, aiming to accelerate recruitment and enrollment into studies and complement local efforts. Method: Adults age 18+ are eligible to join APR at www.endALZnow.org . At enrollment, individuals provide their name, email address, zip/postal code and year of birth; after enrollment they provide additional demographic information at their convenience with the option to select "prefer not to answer." The APR team works with researchers to promote AD‐focused studies to members via its website and email. APR members receive email communication for engagement purposes and are notified when new study opportunities are available. Members interested in a study fill out an online contact form with their name, email address and phone number, review and acknowledge the study's eligibility criteria and authorization for APR to share their contact information with the enrolling study team. The APR team provides enrolling studies with a secure dashboard for tracking referrals. Result: The APR launched in May 2012; as of January 2020, >347, 000 have joined. APR members have a mean age of 63.3 years (SD 11.7), are predominately female (75%), self‐report being cognitively unimpaired (94%), and 50% report a family history of AD/dementia. To date, the APR has promoted 82 AD‐focused studies, results from which will be presented. Only anecdotal enrollment metrics are available prior to the launch of the online contact form, however web‐traffic metrics that are available from our promotions of online studies (e.g., TRC‐PAD, Brain Health Registry) suggest >16, 000 APR members expressed interest in joining these studies. The 6‐month pilot phase of the online contact form included 7 studies and referred 320 APR members. Conclusion: Enrollment into the APR continues to increase, as does the number of studies the APR promotes to its members. We are exploring novel approaches for increasing enrollment and engagement of members, and collaborating with researchers and sponsors to help promote studies in their communities.